2020
DOI: 10.5334/jbsr.2223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Superselective Renal Artery Embolization on Renal Function and Blood Pressure

Abstract: Objectives: To evaluate the effect of superselective renal artery embolization in terms of renal function and blood pressure, to compare the results between groups with different embolization extents, and to analyze risk factors of entire study population for postprocedural acute kidney injury (AKI). Materials and Methods: The inclusion criteria were patients who underwent renal artery embolization from January 2009 to December 2019, with available serum creatinine and blood pressure data. The exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This is in accordance with the literature: Haochen et al reported a mean creatinine value that was not different at 1 day and 1 week after embolization compared with before embolization [ 21 ]; similarly, Dong et al did not find significant differences between serum creatinine before and 7 days after superselective renal arterial embolization) [ 22 ]. On the other hand, Lee et al found chronic kidney disease and a high embolization grade to be predictive factors for postprocedural acute kidney injuries [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the literature: Haochen et al reported a mean creatinine value that was not different at 1 day and 1 week after embolization compared with before embolization [ 21 ]; similarly, Dong et al did not find significant differences between serum creatinine before and 7 days after superselective renal arterial embolization) [ 22 ]. On the other hand, Lee et al found chronic kidney disease and a high embolization grade to be predictive factors for postprocedural acute kidney injuries [ 23 ].…”
Section: Discussionmentioning
confidence: 99%